Gahnite white colour glazes in ZnO–R2O–RO–Al2O3–SiO2 system. Issue 13 (September 2018) - Gajek, Marcin; Partyka, Janusz; Leśniak, Magdalena; Rapacz-Kmita, Alicja; Wójcik, Łukasz
Abstract: The paper focuses on the results of research on the development of newly designed white glazes without the addition of traditional opacifiers such as ZrO2 or ZrSiO4, intended for use in ceramic sanitary products. The effect of opacity was obtained by introducing ZnO in quantities of 4–8 wt% to the sets of glazes. ZnO introduced to the glaze compositions resulted in crystallization of gahnite, and gahnite caused the glaze to become opaque and white. Measurements of the whiteness of glazes confirmed its high level, over 90 units were noticed according to the CIE Lab scale. The microstructure and structure of the glazes were measured by scanning electron microscopy and X-ray diffractometry. The colour and gloss of the glazes were measured using a spectrophotometer and a gloss meter. The topography of the glaze surfaces, as well as the roughness level (Ra), were measured using a confocal microscope.